Induction of supraventricular tachycardias in patients undergoing pulmonary vein isolation for paroxysmal atrial fibrillation is safe and reasonable - Vrtal, Jiri; Plasek, Jiri; Sipula, David; Vaclavik, Jan; Dodulik, Jozef; Skala, Tomas; Cernicek, Vlastimil (Biomedical papers, 2024)
Aims. Patients with atrial fibrillation (AF) may experience other supraventricular tachycardias (SVT) that can trigger AF and cause similar symptoms. The aim of this study was to assess the safety and effectivity of inducing SVT in patients undergoing catheter ablation (CA) for AF.Methods. In 61 patients with paroxysmal AF undergoing CA between January 2022 and March 2023, an electrophysiological study was performed after pulmonary vein isolation (PVI) to induce SVT. Induced arrhythmias were mapped and ablated. All patients were followed up at 3, 6, and 12 months after the procedure; seven-day ECG Holter monitoring was carried out 6 and 12 months after the procedure.Results. In 24 patients (39%) an SVT was induced during the stimulation protocol. There was no significant difference in procedure time (P=0.408) or fluoroscopy dose (P=0.458) between patients with and without inducible arrhythmia. Further, none of the echocardiographic variables such as left atrial volume index (LAVI) (P=0.936), left ventricular ejection fraction (LVEF) (P=0.586), or right atrial (RA) area (P=0.716), differed significantly in these subgroups. Age was a significant factor in patients with arrhythmia inducibility compared with those without (64.5 ± 7.6 and 58.2 ± 10.5, P=0.04).Conclusion. SVT inducibility after successful PVI was 39%. Ablation of nonclinical arrhythmia is safe and did not prolong the total procedure or fluoroscopy time.
Keywords: atrial fibrillation; supraventricular tachycardias; inducibility; ablation